Diversity of Soil Macrofauna at Different Stages of the Age of Sengon's Stand in Jatirejo, Kediri - SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2000)
Soil fauna have important roles on increasing and maintaining soil productivity through it's function on organic decomposition processes, and optimizing physics, chemist and biology of soil characters. The research was conducted to investigate structure of the community of soil macrofauna from different stages of the age of sengon's (Paraserianthes falcataria) stand in wet season of year 2000. Pit fall trap and hand-shorting methods were used to catch soil macrofauna. Sampling was done on 8 different age stages (year) of sengon plant each with triplicate repetition. Twenty-seven macrofauna species in the soil and 26 macrofauna species in soil surface were found in this study. Those species belong to the phylum of Mollusc, Annelid and Arthropod. Pontoscolex sp and Lobopelta ocellifera were species that having high important value. Similarities analysis resulting in an index of 65% indicating low level of diversity differences among soil macrofauna from different ages of the sengon stand. Simple correlation analysis indicates that macrofauna diversity in the soil was closely related with soil organic content, domination of ground vegetation and soil humidity; while macrofauna diversity of soil surface was closely related with the level of light penetration.